Imunodiagnóstico da toxocaríase humana com antígeno TES30 recombinante - Telmo, Paula de Lima (2013)
The toxocariasis is a widespread zoonosis worldwide, thus becoming an important public health problem. The diversity of clinical conditions associated with the different sites (liver, lungs, brain, eyes, lymph nodes, etc.) of the Toxocara canis larvae in the human body, hamper the diagnosis of this disease. In this context, immunological methods for detecting anti-T. canis serum antibodies were developed. Currently, enzyme-linked immunosorbent assay (ELISA) associated with the excretorysecretory antigens of T. canis larvae (TES), and sera previously adsorved with somatic antigen of Ascaris spp. has been used as a standard method for testing of IgG anti-T. canis serum antibodies. The antigen TES is obtained from T. canis larvae cultivation and demand four months of expensive and laborious work. Given the above, recombinant antigens are being tested, aiming at improving the immunodiagnosis of human toxocariasis. The objective of this work was to produce recombinant excretion/secretion 30kDa T. canis larval antigen (TES30) in two heterologous protein expression systems, and evaluate them in the immunodiagnosis of human toxocariasis. The recombinants proteins rTES30E and rTES30P, respectively, produced in Escherichia coli and Pichia pastoris, were characterized by un indirect ELISA to detect anti-T. canis IgG in experimentally infected mice serum, which showed 100% effectiveness compared to native TES. For detecting anti-T. canis IgG antibodies in human sera, the rTES30E showed sensitivity and specificity (95% CI) of 95.8% and 82.6%, while rTES30P showed 95.4% and 92.8%, respectively, in comparison to native TES. Thus, we conclude that both recombinants proteins have antigenic potential, becoming an alternative to the use of native TES in immunodiagnosis of human toxocariasis.